Baroreflex Sensitivity Impairment During Hypoglycemia: Implications for Cardiovascular Control - Rao, Ajay D. (Diabetes, 2016)
Studies have shown associations between exposure to hypoglycemia and increased mortality, raising the possibility that hypoglycemia has adverse cardiovascular effects. In this study, we determined the acute effects of hypoglycemia on cardiovascular autonomic control. Seventeen healthy volunteers were exposed to experimental hypoglycemia (2.8 mmol/L) for 120 min. Cardiac vagal baroreflex function was assessed using the modified Oxford method before the initiation of the hypoglycemic-hyperinsulinemic clamp protocol and during the last 30 min of hypoglycemia. During hypoglycemia, compared with baseline euglycemic conditions, 1) baroreflex sensitivity decreases significantly (19.2 ± 7.5 vs. 32.9 ± 16.6 ms/mmHg, P < 0.005), 2) the systolic blood pressure threshold for baroreflex activation increases significantly (the baroreflex function shifts to the right; 120 ± 14 vs. 112 ± 12 mmHg, P < 0.005), and 3) the maximum R-R interval response (1,088 ± 132 vs. 1,496 ± 194 ms, P < 0.001) and maximal range of the R-R interval response (414 ± 128 vs. 817 ± 183 ms, P < 0.001) decrease significantly. These findings indicate reduced vagal control and impaired cardiovascular homeostasis during hypoglycemia.